Influence Discipline and Learning Independence on Students' Economic Learning Outcomes Class XI in Pematang Siantar 2 Public High School - Sion Andreas Simanjuntak; Binsar Tison Gultom; Anton Luvi Siahaan (MultiTech Publisher, 2023)
This research aims to determine the influence of discipline and independent learning on student learning outcomes in class XI economics subjects at SMA Negeri 2 Pematang Siantar. The variables in this research are learning discipline and learning independence as independent variables and learning outcomes as the dependent variable. This type of research is quantitative research with a quantitative descriptive approach, with a research population of class XI students at SMA Negeri 3 Pematang Siantar and a research sample of class Data collection techniques use instruments: (1) discipline questionnaire, (2) learning independence questionnaire, and (3) learning outcomes questionnaire. ​The results of this research show that: (1) there is a positive and significant influence of learning discipline on learning outcomes. This result can be seen in the t test where the calculated t value of parental attention (3.374) > t table value (1.67528) which means that the variable is significant. (2) there is a positive and significant influence of interest in learning on learning achievement (3.272) > t table value (1.67528) which means this variable is significant. (3) Parental attention and interest in learning together influence learning achievement, this result can be seen in the F test where the calculated F value (6.600) is > compared to the F table value (2.79). The R Square coefficient of determination test was found to be 0.216, meaning that 21.6% of the variables of parental attention and interest in learning had an influence on student learning achievement at SMA Negeri 3 Pematang Siantar and the remaining 78.4% was the influence of other variables not examined in this research.